2925. A property of 37 - Roger North (The Mathematical Gazette, 1960)
Aims and background Autologous plasma-based fillers have gained interest in regenerative aesthetics as biologically active alternatives to conventional dermal fillers. However, conventional PRP-Gel formulations may be limited by rapid degradation, variable bioactivity, and insufficient structural persistence. This study aimed to evaluate ExoFiller, an activated and concentrated platelet-rich plasma (PRP)-based biofiller, in comparison with conventional PRP-Gel. Technology ExoFiller was prepared through controlled mechanical activation, concentration, filtration, and thermal restructuring of PRP to combine platelet-derived bioactive mediators with structural plasma proteins in a filler matrix. Patient selection A pilot clinical application was performed in 20 patients aged 20 to 65 years presenting with facial volume loss, scarring, or aesthetic rejuvenation demands. Patients were evaluated by dermatological examination and medical history screening before treatment. Techniques ExoFiller and PRP-Gel were assessed using swelling behavior analysis, degradation analysis, in vitro cytocompatibility testing with human dermal fibroblasts, cytokine microarray analysis, and preliminary clinical evaluation. Post operative care Patients were advised to avoid excessive facial manipulation, heat exposure, strenuous exercise, and additional aesthetic procedures immediately after treatment. Current and future development ExoFiller demonstrated improved swelling capacity, slower degradation, favorable fibroblast viability, and increased levels of regenerative mediators compared with PRP-Gel. Preliminary clinical observations suggested improvements in facial volume, contour, and skin quality without adverse effects. Conclusion and clinical relevance ExoFiller showed improved stability, cytocompatibility, and regenerative potential compared with conventional PRP-Gel. By integrating structural plasma proteins with platelet-derived bioactive components, this approach may provide a biocompatible and durable autologous option for soft tissue augmentation and aesthetic tissue regeneration.